2018
DOI: 10.1016/j.vetmic.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes associated with bovine periodontitis and oral health

Abstract: Periodontitis is an infectious polymicrobial, immuno-inflammatory disease of multifactorial aetiology that has an impact on the health, production and welfare of ruminants. The objective of the present study was to determine the microbial profiles present in the gingival sulcus of cattle considered periodontally healthy and in the periodontal pocket of animals with periodontitis lesions using high-throughput bacterial 16S rRNA gene sequencing. Subgingival biofilm samples were collected from 40 cattle with peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 37 publications
4
55
0
Order By: Relevance
“…Mollicutes class and Archaea domain, in humans and animals, are present in healthy patients with gingivitis, necrotizing gingivitis, or periodontitis (Yamabe et al 2008, Faveri et al 2011, Griffen et al 2012, Chen et al 2015, Harris et al 2015. In cattle with periodontitis, Mollicutes class is more often associated with the disease (Borsanelli et al 2018). In the calves in the present study, class Mollicutes was detected in sites with gingivitis and necrotizing gingivitis, and it can be noted that this microorganism was present in the different phases of periodontal diseases.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Mollicutes class and Archaea domain, in humans and animals, are present in healthy patients with gingivitis, necrotizing gingivitis, or periodontitis (Yamabe et al 2008, Faveri et al 2011, Griffen et al 2012, Chen et al 2015, Harris et al 2015. In cattle with periodontitis, Mollicutes class is more often associated with the disease (Borsanelli et al 2018). In the calves in the present study, class Mollicutes was detected in sites with gingivitis and necrotizing gingivitis, and it can be noted that this microorganism was present in the different phases of periodontal diseases.…”
Section: Discussionsupporting
confidence: 53%
“…As multifactorial infectious diseases, periodontal diseases are non-linear processes, external to the organism but associated with the bacterial biofilm adhered to the tooth and planktonic microbiota (Socransky & Haffajee 2005, Borsanelli et al 2018. In this approach, the action of virginiamycin probably has been in the promotion of bacterial homeostasis favorable to the maintenance of periodontal health or in the prevention of dysbiosis, which causes the onset of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several species of potential periodontopathogens have recently been identified in bovine periodontal lesions by PCR, including spirochaetes and black-pigmented anaerobic bacteria (Borsanelli et al, 2015a;Borsanelli et al, 2015b). We have recently shown that the key genera associated with bovine periodontitis are Prevotella, Fusobacterium and Porphyromonas (Borsanelli et al, 2018), genera which are also associated with human periodontitis. Therefore, it is likely that members of these genera may be important in the activation of TLRs observed in this study.…”
Section: Discussionmentioning
confidence: 99%